Analisis Kelayakan Investasi Perancangan Alat Pembuat Adonan Mie Ayam - Nasrullah, Muhammad Iqbal; Yuwono, Istantyo; Putri, Erni Puspanantasari (Fakultas Teknik Universitas Tulang Bawang, 2025)
Pak Pon's chicken noodle SME is a business that sells chicken noodles located in Surabaya. This SME operates by selling only one menu item, chicken noodles, with an average of 200 kg of noodles sold per month, and it still purchases its noodle ingredients from suppliers. Therefore, none of the processes in this SME use machines to prepare the ingredients for the chicken noodles. Given this situation, the researcher has an idea to create a tool that can help streamline the production process in this SME with the aim of increasing sales profit. This research uses cost analysis methods to determine the cost of production, followed by the NPV method to assess whether the equipment purchased by the SME is feasible. The results of this research show that there is a comparison between making the ingredients in-house versus purchasing them. The investment in equipment for the SME is considered feasible, as the payback can be achieved in a few months. This study recommends that the SME increase its sales beyond 200 kg per month in order for the project to proceed as planned. Keywords: Cost analysis, Noodle Dough Tool, NPV, Profit